Paradox Lost? - Richard A. Easterlin (Institute for the Study of Labor (IZA), 2016)
Or Paradox Regained? The answer is Paradox Regained. New data confirm that for countries worldwide long-term trends in happiness and real GDP per capita are not significantly positively related. The principal reason that Paradox critics reach a different conclusion, aside from problems of data comparability, is that they do not focus on identifying long-term trends in happiness. For some countries their estimated growth rates of happiness and GDP are not trend rates, but those observed in cyclical expansion or contraction. Mixing these short-term with long-term growth rates shifts a happiness-GDP regression from a horizontal to positive slope.
Keywords: I31; D60; O10; O5; 330; Easterlin Paradox; economic growth; income; happiness; life satisfaction; subjective well-being; transition countries; less developed nations; developed countries; long-term; short-term; trends; fluctuations